The Bactericidal Activity of Carbon Monoxide-Releasing Molecules against Helicobacter pylori - Tavares, A.F. (2014)
Helicobacter pylori is a pathogen that establishes long life infections responsible for chronic gastric ulcer diseases and a proved risk factor for gastric carcinoma. The therapeutic properties of carbon-monoxide releasing molecules (CORMs) led us to investigate their effect on H. pylori. We show that H. pylori 26695 is susceptible to two widely used CORMs, namely CORM-2 and CORM-3. Also, several H. pylori clinical isolates were killed by CORM-2, including those resistant to metronidazole. Moreover, sub-lethal doses of CORM-2 combined with metronidazole, amoxicillin and clarithromycin was found to potentiate the effect of the antibiotics. We further demonstrate that the mechanisms underpinning the antimicrobial effect of CORMs involve the inhibition of H. pylori respiration and urease activity. In vivo studies done in key cells of the innate immune system, such as macrophages, showed that CORM-2, either alone or when combined with metronidazole, strongly reduces the ability of H. pylori to infect animal cells. Hence, CORMs have the potential to kill antibiotic resistant strains of H. pylori.